Thermal properties of silver/graphite composites with different volume ratio processed by pulsed current activated sintering method. (4th May 2021) - Jang, Jun-Ho; Park, Hyun-Kuk; Lee, Jeong-Han; Lim, Jae-Won; Oh, Ik-Hyun
Abstract : This study focuses on the effect of the volume fraction of Ag and graphite (Gr) on the thermal conductivity (TC) and coefficient of thermal expansion (CTE) of Ag-Gr composites. Graphite flake (GF) powder was coated with Ag through electroless plating (EP) method and was then sintered using pulsed current activated sintering (PCAS) method. The anisotropy Gr has different characteristics depending on the bonding direction. The unidirectional orientation rate (UOR) of the GF powder in the vertical direction was as high as 98%. The measured TC and CTE values of Cu-Gr composites were 540–580 W/mK and 9–15 ppm/K, respectively.